2021
DOI: 10.1155/2021/6492289
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Seven Reproductive Diseases in Beef and Dairy Cows from Three Provinces in Indonesia

Abstract: Bovine reproductive diseases are endemic in Indonesia, but comprehensive information about their infectious causes is not available. Therefore, our aim for this study was to detect several infectious agents that cause reproductive diseases in Indonesian beef and dairy cows. A total of 152 cow serum samples collected by Faculty of Veterinary Medicine of Brawijaya University and Veterinary Disease Investigation Centre as a part of the mandatory and regularly surveillance system from three provinces during 2019–2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 45 publications
1
7
0
Order By: Relevance
“…Provinces in Java are endemic areas, as many studies confirmed seroconversion and antigen detection [39][40][41][42][43][44][45][46]. Seroconversion to BVDV was also detected in cattle in Southern Papua, East Nusa Tenggara, West Nusa Tenggara Barat, Bali and Lampung [62,64,65]. Seroconversion of BVDV was detectable in an outbreak of cattle diarrhoea in West and South Kalimantan in 1989 [32,33].…”
Section: Prevalencementioning
confidence: 98%
See 3 more Smart Citations
“…Provinces in Java are endemic areas, as many studies confirmed seroconversion and antigen detection [39][40][41][42][43][44][45][46]. Seroconversion to BVDV was also detected in cattle in Southern Papua, East Nusa Tenggara, West Nusa Tenggara Barat, Bali and Lampung [62,64,65]. Seroconversion of BVDV was detectable in an outbreak of cattle diarrhoea in West and South Kalimantan in 1989 [32,33].…”
Section: Prevalencementioning
confidence: 98%
“…The study in Java that revealed a PI prevalence of 6% in dairy cows with low reproductive performance [49] also indicated that the level of transient infection from PIs to other naive cows could have been high and caused reproductive problems. Several other bovine reproductive diseases are endemic in Indonesian cattle, including Infectious Bovine Rhinotracheitis, trichomoniasis, leptospirosis, bovine brucellosis, babesiosis, anaplasmosis and theileriosis [65,[69][70][71]. Coinfections with BVDV and other reproductive pathogens in cattle were also reported [65].…”
Section: Impact Of Bvd On Cattle Production In Indonesiamentioning
confidence: 99%
See 2 more Smart Citations
“…Reproductive diseases represent the main cause of economic losses in dairy and beef cattle (Bos taurus) production [19]. Abortions and stillbirths in productive animals are estimated to represent an approximated cost between USD 500 and 900 per case [3,11].…”
Section: Introductionmentioning
confidence: 99%